Open: Lymphoma Risk and Overall Safety Profile of Adalimumab in Patients With Crohn's Disease With up to 6 Years of Follow‐up in the PYRAMID Registry. (June 2018) - D'Haens, Geert; Reinisch, Walter; Panaccione, Remo; Satsangi, Jack; Petersson, Joel; Bereswill, Mareike; Arikan, Dilek; Perotti, Eva; Robinson, Anne M; Kalabic, Jasmina; Alperovich, Gabriela; Thakkar, Roopal; et al.
Abstract : OBJECTIVES: Real‐world, prospective, long‐term studies in Crohn's disease (CD) characterizing adalimumab safety data and lymphoma risk were lacking. We present the final results from the PYRAMID registry, which was designed to rule out a doubling of lymphoma risk in adalimumab‐treated patients with CD. METHODS: Patients with moderately to severely active CD newly prescribed or currently receiving adalimumab according to local product labels were followed for up to 6 years and analyzed for adverse events (AEs). The registry exposure‐adjusted observed rate of lymphoma was compared with the estimated background lymphoma rate from a sex‐matched general population in the Surveillance, Epidemiology, and End Results 17 Registry database adjusted for anticipated prior or concurrent thiopurine use in a CD population. RESULTS: A total of 5025 patients were evaluated (16680.4 PY of adalimumab registry exposure, ≈3 years/patient mean follow‐up). Registry treatment‐emergent AEs included 4129 serious AEs ( n = 1853 [36.9%]; 24.8 E/100 PY), 792 serious infections ( n = 556 [11.1%]; 4.7 E/100 PY), and 134 malignancies ( n = 116 [2.3%]; 0.8 E/100 PY), including ten lymphomas. The observed lymphoma rate (0.060 E/100 PY) was lower than the estimated background rate (0.084 E/100 PY), and the upper bound of the one‐sided 95% CI of the observed rate (0.102 E/100 PY) was lower than double the estimated rate (0.168 E/100 PY). CONCLUSIONS: PYRAMID is the longest prospective adalimumab study in routine clinical practice, with up to 6 years of follow‐up. No new safety signals were reported. The pre‐specified registry objective of ruling out a doubling of lymphoma risk with adalimumab was met. SUPPLEMENTARY MATERIAL accompanies this paper at https://doi.org/10.1038/s41395–018–0098–4